An X‐ray spectroscopic perspective on Messinian evaporite from Sicily: Sedimentary fabrics, element distributions, and chemical environments of S and Mg. (21st April 2016) - Yoshimura, Toshihiro; Kuroda, Junichiro; Lugli, Stefano; Tamenori, Yusuke; Ogawa, Nanako O.; Jiménez‐Espejo, Francisco J.; Isaji, Yuta; Roveri, Marco; Manzi, Vinicio; Kawahata, Hodaka; Ohkouchi, Naohiko
Abstract: The Messinian salinity crisis is a dramatic hydrological and biological crisis that occurred in the Mediterranean basin at 5.97–5.33 Ma. The interpretation of the facies and stratigraphic associations of the Messinian salt deposits is still the object of active research because of the absence of modern depositional analogues of comparable scale. In this study, the spatial distributions of Na, Mg, S, O, Si, and Al in a potassic‐magnesian salt and a halite layers of Messinian evaporites from the Realmonte mine on Sicily were determined using synchrotron based micro‐X‐ray fluorescence. The dominant molecular host site of Mg and S obtained by X‐ray absorption near edge structure (XANES) is applied to specify the hydrochemistry of hypersaline brines and the presence of diagenetic minerals, thus shedding light on evaporative concentration processes in the Caltanissetta Basin of Sicily. Mg and S K ‐edge XANES spectra revealed the presence of highly soluble Mg‐bearing sulfates. The massive halite layer "unit C, " contains less soluble minerals, thus did not exceed the stage of halite crystallization. We infer that as evaporative concentration increased, the density of the brine at the shallow margin of the basin increased as salinity increased to concentrations over 70 times the starting values, creating brines that were oversaturated with Mg‐sulfate. Density stratification of the deep basin caused heavy brines to sink to the bottom and become overlain by more dilute brines. We propose lateral advection of dense Mg‐sulfate brines that certainly affected marine biota. Key Points: Microscale distributions of soluble sulfate minerals in MSC evaporites were described A depositional environment is proposed with marked brines density stratification Evaporative concentration likely promoted a serious impact on the biota in the Caltanissetta basin